Does learning interest predict academic performance in an interest-driven HyFlex course? - Teh, Liang Jing; Wong, Su Luan; Abdul Rani, Mohd Zariat; Md Khambari, Mas Nida; Tang, Sai Hong (Asia-Pacific Society for Computers in Education, 2024)
Learning interest has been found to have insignificant and significant relationships with academic performance among students. This study aims to examine the association between learning interest and academic achievement among undergraduate students who underwent a Hybrid-flexible (HyFlex) course which was designed and implemented based on the interest loop of Interest-driven Creator (IDC) theory. In the HyFlex learning setting, students had the autonomy to learn physically, online synchronously, or online asynchronously for each class session. 48 undergraduate students from the faculty of education at a public university in Malaysia participated in this study. Pearson correlation analysis shows a significant positive correlation between learning interest and academic performance. A simple linear regression analysis found that learning interest contributed significantly to academic performance. This implies that the integration of the IDC theory into HyFlex learning could have the potential to foster interest and enhance performance among undergraduate students. However, the small effect size of learning interest indicates that while it is pertinent to cultivate learning interest among learners, academic achievement could be affected by other factors beyond interest.